Public health and clinical approach to proactive prevalence of symptoms-based diagnosis of mild sarsCoV-2 infection in southern tuscany - Scalese, M.; Trivellini, G.; Sposato, B. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. To date, it is unknown how many Italians have had or have a mild sars-CoV-2 infection, because of the lack of epidemiological studies involving the general population. Study design. Aim of this study was to investigate the prevalence/incidence of a symptoms-based mild sarsCoV-2 infection in southern Tuscany, by using an online survey. Methods. An anonymous random middle-aged sample of 3,460 individuals completed the survey. A symptomscore ≥5, calculated on 195 patients with RT-PCR COVID-19 disease (sensitivity/specificity of 0.815/0.780 respectively) was used for the diagnosis. Results. This cut-off highlighted that 12.3% of all the population might have had a sars-CoV-2 infection, while 3.9% of them might have it at the time of the survey. Female sex (OR=1.334 [1.029-1.728]; p=0.030), obesity status (OR=1.961 [1.304-2.949]; p=0.001), asthma (OR=2.035 [1.433-2.890]; p=0.0001), autoimmune diseases (OR=2.103 [1.381-3.201]; p=0.001), were all risk factors for showing mild sars-CoV-2 infection. Instead, the elderly had a low probability to develop mild forms of the disease (OR=0.984 [0.9750.994]; p=0.001).Conclusion: A remarkable number of subjects in Southern Tuscany may have already had a mild SARSCoV-2 infection. Symptoms scores might be used to screen subjects with a suspected infection. Female sex, obesity, asthma, autoimmune diseases may be factors linked with mild forms of COVID-19 disease.